Democratis Values Require New Strategies - Wisaksono Noeradi (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2009)
For more than 30 years Indonesians were ruled under “Demokrasi Pancasila” favored by the Suharto administration. In-spite of the fact that Indonesia enjoyed economic stability, freedom of expression voicing an opinion not to the administration’s best interest was not tolerated. The nation knew only general elections where participating politicians were nominated by one of the three politicalparties. Publicexecutiveswereappointedbytherulingparty. Demonstrationswererepressed through various security regulations, if not by means of force. Being part of Angkatan Bersenjata Republik Indonesia (ABRI, Armed Forces of the Republic of Indonesia), the police depended heavilyonthemilitary’ssupportinrestoringpublicsecurity. One-waycommunicationwastheorder of the day. It was an easy life indeed for the public sector. Obviously, the monetary crisis which hit the country in mid 1997 brought revolutionary changes into the life of Indonesians too hard for the public sector to believe, never mind to accept. All of the sudden they saw political reform that introducedrealdemocracy. Theimplementationofregionaldecentralizationbroughtalotofconfusion and frustration. As public security became the sole responsibility of the police, the military’s duty shouldbehandlingdefensemattersandprovidingassistanceinemergencysituationsonly. Presidential electionwashelddirectly. Everythingissubjecttomassprotestand demonstrationstagedthroughout the country. Suddenly, the public sector had to adopt new values. They were simply not prepared for the new realities. Wanting to do things the easy way, top managements of the public sector realized that it needed to address the new challenge accordingly. Thus, empowering the internal stakeholders became their priority before communicating with any external stakeholder. How? Tentara Nasional Indonesia (TNI), Kabupaten Kebumen (a level II Administration) in Central Java, and Garuda (a State-owned airline) had their experiences for us to share.